Quantification of methane emissions from typical natural gas stations using on-site measurement technology - Wenlong Jia; Pingyang Jia; Li Gu; Lei Ren; Yang Zhang; Honghuan Chen; Xia Wu; Wei Feng; Jiujiang Cai (Journal of Pipeline Science and Engineering, 2025)
Natural gas transmission systems are the main source of methane emissions in the oil and gas industry. Methane, as the second most potent greenhouse gas, makes a strong contribution to climate change. The hydrogen flame ionization detector and Hi-Flow sampler (a large flow methane detector) technologies were used to measure fugitive methane emissions in five distinct categories of stations in natural gas transmission pipelines in China. The methane emission rate of different components was quantified, enabling a comparison of methane emission characteristics across different stations. The resulting data was used to deduce a correlation equation between the methane concentration and the emission rate of various components. The leakage probability of components in the surveyed stations ranged from 2.54% to 7.77%. Notably, the leakage probability of liquefied natural gas (LNG) terminals was considerably higher than that of the other stations. A one-way analysis of variance revealed significant differences in methane emission rates between components with different processes. The bootstrap method was used to calculate the mean methane emission rates and 95% confidence intervals for each component. The mean methane emission rates and 95% confidence intervals for valves, flanges, connectors and open-ended lines were 26.43 (15.86, 38.56), 35.84 (23.36, 50.19), 4.90 (3.43, 6.73), and 30.76 (18.62, 44.19) kg/a, respectively. In conclusion, the total fugitive methane emissions detected at the LNG terminal and underground gas storage were 5,202.1 and 1,891 kg/a, respectively. There were no significant differences in the emissions of the compressor, distribution, and meter stations on the natural gas transmission trunk pipe, with values between 1,000 and 1,200 kg/a. The bootstrap method, in conjunction with the Monte Carlo method, was used to estimate the fugitive methane emissions in the compressor area of another natural gas compressor station. The estimated result was 1,853.58 kg/a, while the measured value was 1,418.55 kg/a, therefore exhibiting a slight discrepancy.